Functional Studies of Sex Pheromone Receptors in Asian Corn Borer Ostrinia furnacalis - Liu, Wei; Jiang, Xing-chuan; Cao, Song; Yang, Bin; Wang, Gui-rong (Frontiers in Physiology, 2018)
Lepidopteran insects use sex pheromones for sexual communication. Pheromone receptors expressed on peripheral olfactory receptor neurons (ORNs) are critical part to detect the sex pheromones. In genus Ostrinia, several pheromone receptors were functional analyzed in O. nubilalis and O. scapulalis but the knowledge in O. furnacalis was rare. In this study, seven pheromone receptors were deorphanized by heterologous expression system of Xenopus oocytes. Functional types of sensilla trichoidea were classified by single sensillum recordings to interpret the response pattern of olfactory sensory neurons to Ostrinia pheromone components. OfurOR4 and OfurOR6 responded to the major sex pheromone Z/E12-14:OAc. OfurOR4 is the main receptor for both Z/E12-14:OAc and OfurOR6 mainly responded to E12-14:OAc. Functional differentiations of gene duplication were found between OfurOR5a and OfurOR5b. OfurOR5b showed a broad response to most of the pheromone components in O. furnacalis, whereas OfurOR5a was found with no ligands. OfurOR7 showed a specific response to Z9-14:OAc and OfurOR8 mainly responded to Z11-14:OAc and E11-14:OAc. OfurOR3 did not respond to any pheromone components. Our results improved the current knowledge of pheromone reception in Ostrinia species which may contribute to speciation.